Name of Biblical Judge Surfaces - Garfinḳel, Yosef (The Biblical archaeology review, 2022)
An inscription bearing the personal name Jerubba‘al was uncovered in 2019 at Khirbet al-Ra‘i, a small Iron Age site located near Lachish in the Judean Foothills. Written in black ink on a small sherd from a ceramic jug, the inscription was found inside a grain silo dated to the late 12th or early 11th […]